If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = 13x + -114 Reorder the terms: -4 + 3x = 13x + -114 Reorder the terms: -4 + 3x = -114 + 13x Solving -4 + 3x = -114 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -4 + 3x + -13x = -114 + 13x + -13x Combine like terms: 3x + -13x = -10x -4 + -10x = -114 + 13x + -13x Combine like terms: 13x + -13x = 0 -4 + -10x = -114 + 0 -4 + -10x = -114 Add '4' to each side of the equation. -4 + 4 + -10x = -114 + 4 Combine like terms: -4 + 4 = 0 0 + -10x = -114 + 4 -10x = -114 + 4 Combine like terms: -114 + 4 = -110 -10x = -110 Divide each side by '-10'. x = 11 Simplifying x = 11
| 15c-4=12c+5 | | -6x-3=3 | | y=44+6(1-5) | | -4x-5=5x-14 | | 2[1.5m+3]=3.5m-1 | | 3x^2+5=x^2-2 | | y-10=2x+3x | | y=-16+6(1+5) | | 5x+4-10=2x-2 | | 2x+37=12x-73 | | x+9=7x-63 | | y-10=2 | | 6x^2-7x-5=0 | | 3x^2+x=2x-6 | | 3+(-5x)=-17 | | y=94+5(1-9) | | 4(a+3.2)=9a-5.2 | | y=9+5(1+8) | | 4x-5+5x-15=180 | | 6(-4-7a)+4=28+6a | | 2x^2-3x=20 | | 6b-2b+6=-10 | | 205=5(1+5v) | | 8-4d=12 | | y=8+6(1-5) | | -35+7x=8(x-4) | | 2[a-1]=3[a+1] | | 9a-(15a-(3b+7a)+(-8b+a)+12b)= | | y=5+5(1-8) | | 7(x+5)-4=87 | | .6(2m-10)=.6m+10 | | 12-4y=16x |